Longitudinal beam splitting and coalescing using an off-momentum drifting barrier bucket - T. Yoshimoto; M. Hirose; X. Liu; K. Takayama; T. Adachi; K. Okamura; E. Kadokura; T. Kawakubo; S. Takano; N. Munemoto (Physical Review Accelerators and Beams, 2021)
There has been much research on longitudinal bunch splitting and coalescing for accelerator performance improvements in rf synchrotrons. In this paper, we report a scheme with several induction cells that goes beyond the limitation in which the phase drift speed of beam buckets must be much lower than that of the maximum off-momentum particles to minimize longitudinal emittance blowup. In principle, additional pulse acceleration voltages can be applied to produce a momentum jump of the beam and save beam manipulation time, which is crucial for fast-cycling synchrotrons with limited injection and extraction times. This paper compares the new and conventional schemes with experimental results. Finally, the beam behaviors are discussed with macroparticle simulations.